Degree of Organizational Justice among Principals at Al-Qweismeh Primary Schools and its Relationship to Teachers' Loyalty - Ayah Thiab Alabsi (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: This study aims to identify the degree of practice of organizational justice among public primary school principals in Qweismeh District and its relationship to loyalty of teachers to those schools. The study was applied to a sample of (288) male and female teachers who were chosen by a stratified random method. Methods: The researcher developed a questionnaire for organizational justice, and another for organizational loyalty. The validity and reliability of the two questionnaires were verified. Results: One of the most prominent results reveal that the degree of practicing organizational justice among the principals of public primary schools in Al-Qweismeh district and the degree of organizational loyalty among the teachers in those schools were medium. The results also show a positive, direct, statistically significant correlation between the degree of practice of organizational justice among principals of public primary schools in Al-Qweismeh district and the organizational loyalty of teachers in those schools. The results also show that there were statistically significant differences in the degree of practice of organizational justice among school principals due to gender in favor of females, while there were no statistically significant differences due to experience. Conclusions: The researcher recommends that teachers should be given an opportunity to participate more in school work, and to reduce the burden of paperwork placed on the teachers.